The Geoeconomic Turn of the Single European Market? Conceptual Challenges and Empirical Trends - Herranz-Surrallés, Anna; Damro, Chad; Eckert, Sandra (JCMS-Journal of Common Market Studies, 2024)
The nature of global economic interactions is undergoing profound changes. Rising concerns over the security and strategic implications of economic interdependence are leading to what is often defined as a ‘geoeconomic world order’. In framing this Special Issue, this article sets a common conceptual ground to assess whether, how and why the single European market is experiencing such a geoeconomic turn and how EU responses are shaping other international actors in the process. It develops a research agenda to examine (i) the systemic pressures pushing towards geoeconomic responses, (ii) the internal drivers and processes determining the nature of the EU's geoeconomic turn (what we term ‘shades of geopoliticisation’) and (iii) the external consequences of the EU's embrace of geoeconomics. The analytical discussion is complemented by an overview of empirical trends, drawing examples from the various fields of market integration and European policy-making covered in the contributions to this Special Issue.
CRIS-Team Scopus Importer:2024-05-03
Keywords: EU external economic policy; geoeconomics; geopoliticisation; geopolitics; single market